Group Sexual Offending by Juvenile Females. (June 2015) - Wijkman, Miriam; Weerman, Frank; Bijleveld, Catrien; Hendriks, Jan
This study examined all group sexual offending cases in the Netherlands between 1995 and 2009 ( n = 26) in which at least one juvenile female offender ( n = 35) had been adjudicated. Information from court files showed that the majority of juvenile female group sexual offenders have (inter)personal problems and (sexual) abuse experiences. The aims of the offender groups in committing the offense could be categorized in three themes: harassing the victim, sexual gratification, and taking revenge. The reasons why juvenile female offenders participated in a group could be categorized into group dynamics versus instrumental reasons. The findings are contrasted with findings on juvenile male group sexual offenders. Implications of the findings for research and treatment are discussed.